Electrochemical doping of three-dimensional graphene networks used as efficient electrocatalysts for oxygen reduction reaction - Wang, Zhijuan (2016)
Three-dimensional graphene networks (3DGNs) doped with a mono-heteroatom of N or B, or dual-heteroatoms of N and B were fabricated, which exhibit excellent oxygen reduction reaction (ORR) performance. Importantly, the onset potential and current density of N and B co-doped 3DGNs are comparable to those of the commercial Pt (30%)/C catalyst.